Leading For Educational Lives Inviting and Sustaining Imaginative Acts of Hope in a Connected World - Novak, John M.; Armstrong, Denise E.; Browne, Brendan; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2014)
This book is written for the growing number of people (teachers, administrators, support staff, parents, and community members) throughout the world who wish to face the challenges of school leadership in ways that feel right, make sense, and contribute to sustaining defensible educational practices. Using and extending the evolving core ideas of the global inviting school movement, it provides a hopeful approach to educational leadership, management, and mentorship that combines philosophical defensibility, administrative savvy, and illustrative stories. A systematic framework for examining the challenges of educational leadership, the Educational LIVES model, is used to organize the book. It is centred on the idea that leadership is fundamentally about people and the caring and ethical relationships they establish with themselves, others, values and knowledge, institutions, and the larger human and other-than-human world. Emphasized throughout the book are the special quality of relationships needed to appreciate individuals in their uniqueness and the types of messages that intentionally call forth their potential to live educational lives. We call this approach the inviting perspective and offer the experiences of educators from around the world who put imaginative acts of hope into practice daily as they lead, manage, and mentor. Leading for Educational Lives: Inviting and Sustaining Imaginative Acts of Hope in a Connected World is divided into three unequal parts. In Part 1, (3z(BEducational LIVES Seen From an Inviting Perspective,(3y (Bwe offer two orienting chapters that look at the unique nature of education seen as a guiding ideal along with the practical nature of an inviting theory of practice for constructing relationships that call forth deepened human possibilities. The foundations of the inviting approach combined with the Educational LIVES model point to the concrete possibilities for practice in the ten chapters in Part 2, (3z(BImaginatively Leading, Managing, and Mentoring Educational LIVES.(3y (BPart 3, (3z(BDare to Lead for Education,(3y (Bis made up of a convergent chapter that looks at what is involved in artfully speaking up for educational lives, personally and professionally. This book is meant to serve as a text for anyone interested in educational leadership from an inviting ethical perspective, an approach that is being used by a growing number of educators throughout the world. It can serve as a stand-alone text or in conjunction with a more traditional survey text.s
Keywords: Education; Education; Education, general; Electronic books